Identification Of Ethnoscience Studies in Science Learning to Strengthen Cultural Relevance in Primary Education - Annisyah Yuni S; Setiawan Edi Wibowo; Srinita Susanto (Postgraduate, University of Mataram, 2025)
To create contextual and culturally responsive science learning, integrating local knowledge into the curriculum has become increasingly important in ethnoscience. This study aims to analyze ethnoscience studies in science learning in grade IV elementary school and identify ethnoscience aspects contained in the learning material. The research method used is a qualitative description, where the researcher acts as the main instrument by using additional instruments in the form of library study guides and documentation. Data collection techniques were carried out through library research with a qualitative data analysis approach which includes three stages: data reduction, data presentation, and conclusion drawing. To test the validity of the data, a triangulation technique of reference sources that have a correlation with the topic under study was used, such as journals, articles, books, and other documents. The results of this study show that ethnoscience studies have been integrated in science learning in grade IV elementary schools, especially in certain themes. In theme 1, for example, ethnoscience studies are related to sound material and associated with cultural values through the introduction of traditional musical instruments, such as angklung, saluang, harp, drum, and tifa. Meanwhile, in theme 7 and theme 8, which discuss style and movement, cultural values are integrated through learning traditional dance movements, such as plate dance, candle dance, and padupa dance. These findings highlight the potential of ethnoscience to enrich science education by connecting scientific concepts with local cultural practices, fostering a deeper understanding of both the natural world and cultural heritage.